(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India is responsible for at least 25 percent of all maternal fatalities recorded abroad since theSafe Motherhood Initiative commenced. India’s objective is to decrease maternal mortality to less than 100per 100,000 live births, yet despite its programmatic efforts and swift economic development over theprevious 20 years, that target is still far away. Maternal mortality varies among the states due to geographyand sociocultural variety, making it unable to execute health sector reforms uniformly. The case studyexamines national trends in maternal mortality, the delivery of healthcare to mothers at various levels, andthe execution of national maternal health initiatives, including more recent cutting-edge tactics.It suggestsimproving the reporting of maternal fatalities and putting evidence-based, targeted measures intopractise, combined with efficient monitoring for quick progress. Additionally, it emphasises the necessityof private sector regulation and calls for more public-private collaborations and policies, as well as astrong political commitment and enhanced managerial skills for enhancing maternal health.